The Distributional Bias of Public Education : Causes and Consequences - Gradstein, Mark (IMF Working Papers; Working Paper ;, 2004)
While public education is often intended to be progressive in its effects on income distribution, in reality its incidence is often skewed toward the rich. This paper argues that the extent of this bias is directly related to institutional weaknesses in governance. We present a simple dynamic model where weak governing institutions allow the rich to be more effective in appropriating a larger share of public education spending thereby preventing inequality reduction. The empirical part provides tentative support for this view, showing that the progressiveness of public education spending is related to the strength of governance.